Sharof Rashidov's Role in Cold War Diplomacy: A Soviet Uzbekistan Perspective - Sanjarbek Numonzoda (PT FORMOSA CENDEKIA GLOBAL, 2023)
After World War II, the Soviet Union gained significant international prestige, which required a comprehensive approach to foreign policy. Newly liberated nations in Africa and Asia, seeking to break free from enduring colonial legacies, became a crucial battleground for Soviet propaganda. Over time, this trend gained momentum, leading to new approaches in Soviet diplomacy. Satellite states and non-Kremlin individuals played an active role in shaping Soviet foreign policy. The case of Soviet Uzbekistan, led by Sharof Rashidov, is particularly notable. Rashidov's exceptional diplomatic skills allowed him to play a prominent role in key events during the Cold War era, guiding his country for 24 years. The main goal of this study is to determine if there was a powerful and semi-autonomous actor outside of the Kremlin, shedding light on the complexities of decentralized involvement within the Soviet geopolitical landscape.